Achieving carbon neutrality in an emerging oil-producing country: Renewable energy transition and international trade flows in Ghana - Clement Oteng; Camara Kwasi Obeng; Pius Gamette (Research in Globalization)
Over the past decade, climate variabilities have emerged as shaping the dynamics of international trade. The adverse externalities posed by climate change require a corresponding improvement in the production of food, trade and the adoption of abundant renewable energy resources. Our study focused on evaluating the impact of renewable energy transition on international trade flows in Ghana. We employed the dynamics ARDL simulation model to analyse our results using data from various institutions. We found that energy transition using both low carbon energy and renewable energy in electricity generation by 1% and 5% significantly increases the balance of trade to the 4th year after which energy transition decreases the balance of trade to the 9th year. After the 9th year, energy transition by both percentages increases the trade balance of Ghana. We observe that the energy transition by 5% has a higher impact than the energy transition by 1%. Additionally, it is observed that using the share of renewable energy in electricity generation has a decreasing rate relative to the first four years. Drafting renewable energy plans such as allocation of funds, supportive policy frameworks and incentives such as green financing, subsidies, and tax incentives can enhance and develop renewable energy infrastructure to increase renewable energy efficiency and reliability for international trade.